UMP collaborates with PETRONAS in the Higher Education Strategic Initiatives CHESS - Mimi Rabita, Abdul Wahit (2023)
KUALA LUMPUR, June 3, 2023 - Universiti Malaysia Pahang (UMP) and Petroliam Nasional Berhad (PETRONAS) recently exchanged Memorandum of Understanding (MoU) documents to facilitate the implementation of the Higher Education Strategic Initiatives (CHESS) program as a catalyst for industry-academic knowledge sharing in the technical field.